Assessing Energy Consumption, Optical Distributions, and Carbon Contaminations using the Design-Builder Simulation Model (Case Study: A Sports Building, Mashhad, Iran) - Nasim Ghadami; Maryam Siamaki; Hossein Pouresmaeil; Reza Aghlmand; Mohammad Gheibi (Annals of Environmental Science and Toxicology - Peertechz Publications, 2021)
Today, optimization and management of energy consumption are considered as one of the main necessities of operating various buildings. Given the decline in production sources of primary energy as well as the produced contaminations due to their consumption, attention toward such matter has doubled. One of the operational solutions to controlling energy consumption is to employ and utilize simulation approaches. In this study, a sports building complex including three separate halls in Mashhad was simulated using the Design-Builder model. The results of thermal simulations showed that parameters such as walls, glasses, and the roof involve almost the same amount of energy loss. Meanwhile, the energy loss due to external infiltration exchanges of the building leads to the highest extent of energy loss, with a rate of 66.28 KBTU/h. Furthermore, at the end of the study, the relationship between the production of carbon dioxide contaminant and the electrical energy consumption for cooling was indicated and examined. Moreover, assessment and zoning were carried out on how optical distribution resulted from solar radiation takes place in the sports building.